2011
DOI: 10.1021/je200178b
|View full text |Cite
|
Sign up to set email alerts
|

Activity Coefficients of RbF or CsF in the Ethene Glycol + Water System by Potentiometric Measurements at 298.15 K

Abstract: In this work, we report the measurements of the thermodynamic properties of RbF or CsF in the ethene glycol + water system at 298.15 K in the range of w = 0.10 to 0.40 ethene glycol. The experimental data were calculated by Pitzer model. Standard cell potentials and Pitzer parameters were obtained. From these, mean activity coefficients of RbF or CsF, osmotic coefficients of the mixtures, and standard Gibbs energies of transfer of RbF or CsF from water to ethene glycol + water mixtures were calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In the previous study, we reported the activity coefficients of LiCl, RbCl, CsCl, RbF, and CsF in alcohol–water mixtures. , As an extension of our work, the ternary systems CsBr–MeOH–water and CsBr–EtOH–water at 298.15 K were studied in this paper. The activity coefficients (γ ± ), osmotic coefficients (Φ), excess Gibbs free energies ( G E ), and standard Gibbs energies of transference (Δ G t 0 ) for CsBr in MeOH–water and EtOH–water mixed solvent systems are presented, while the mass fraction of alcohol in the mixture ( w ) was varied between 0 and 0.3.…”
Section: Introductionmentioning
confidence: 89%
“…In the previous study, we reported the activity coefficients of LiCl, RbCl, CsCl, RbF, and CsF in alcohol–water mixtures. , As an extension of our work, the ternary systems CsBr–MeOH–water and CsBr–EtOH–water at 298.15 K were studied in this paper. The activity coefficients (γ ± ), osmotic coefficients (Φ), excess Gibbs free energies ( G E ), and standard Gibbs energies of transference (Δ G t 0 ) for CsBr in MeOH–water and EtOH–water mixed solvent systems are presented, while the mass fraction of alcohol in the mixture ( w ) was varied between 0 and 0.3.…”
Section: Introductionmentioning
confidence: 89%
“…Water used in experiment was doubly distilled water, and the specific conductance was approximately (1.0 to 1.2)·10 –4 S·m –1 . Details of the potentiometric measurements and general techniques were the same as previously described in our previous work. , …”
Section: Methodsmentioning
confidence: 99%
“…Details of the potentiometric measurements and general techniques were the same as previously described in our previous work. 16,17 The Rb ion-selective electrode (Rb-ISE) and Cs ion-selective electrode (Cs-ISE) were a PVC membrane type based on valinomycin and were filled with 0.10 mol•L −1 RbF or CsF as the internal liquid in K ion-selective electrode. Both the membrane electrode and the F-ISE (model 201) were obtained from Jiangsu Electroanalytical Instrument Co., and the electrodes were calibrated before the experiment and showed a good Nernstian response.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation